Penyuluhan Pemanfaatan Pekarangan Untuk Tanaman Budidaya Bagi Masyarakat Hutan Desa Domato, Halmahera Barat - Ryadin, Aisjah Rachmawaty; Salatalohy, Asiah; Shadikin Nurdin, Aqshan (Jurnal Pengabdian Masyarakat Hutan, 2024)
Counseling the community around the forest on using home yards to plant horticultural crops is very important to maintain sustainable forests and reduce forest encroachment and massive logging. In this time of community empowerment, socialization was fulfilled through the counseling of the utilization of yards of households in Domato Village, which is a village near the Bird Bidadari Observation Forest, South Jailolo District, West Halmahera Regency, where part of this forest area will be employed as a Forest Area for Special Purpose in Education (KHDTK) by the Forestry Study Program, Faculty of Agriculture, Khairun University. Based on the results of this activity, the knowledge of the local community still has to be improved regarding the effectiveness of planting in house yards. Therefore, more intensive counseling is required to encourage local households to utilize their home yards to meet their food needs. Keywords: counseling, Domato village, forest community, food, yards